Accelerated Orthodontic Treatment using Biomodulation: A Randomized Clinical Trial - Avirachan Tara V; Brijesh S; Jerald Arun Bosco; Sreelatha Mahima Anilkumar; Lipare Sukumar V (Wolters Kluwer Medknow Publications, 2024)
BackgroundOrthodontic treatment often spans several months or even years, which can be burdensome for patients. Biomodulation techniques have emerged as potential strategies to expedite orthodontic tooth movement. Materials and MethodsA randomized clinical trial was conducted with a sample of 60 orthodontic patients, aged 12-30 years, requiring fixed appliance therapy. Patients were randomly assigned to either the biomodulation group (n = 30) or the control group (n = 30). The biomodulation group received low-level laser therapy (LLLT) along with traditional orthodontic treatment, while the control group received conventional orthodontic treatment without LLLT. Treatment duration, pain perception, and orthodontic tooth movement were assessed during the study period. ResultsThe results demonstrated a significant reduction in treatment duration in the biomodulation group compared to the control group. The biomodulation group exhibited a 30% reduction in overall treatment time, with an average treatment duration of 8.4 months, while the control group required an average of 12 months (P < 0.001). Pain perception during orthodontic adjustments was lower in the biomodulation group. Additionally, biomodulation was associated with a statistically significant increase in the rate of tooth movement, as evidenced by a 20% reduction in the time required to achieve desired tooth alignment (P < 0.01). ConclusionBiomodulation through low-level laser therapy represents a promising adjunct to traditional orthodontic treatment, significantly accelerating tooth movement and reducing treatment duration.